1999
DOI: 10.1046/j.1525-1497.1999.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in patients’ perceptions of debilitated health states

Abstract: OBJECTIVE:To determine health utility scores for specific debilitated health states and to identify whether race or other demographic differences predict significant variation in these utility scores. DESIGN: Utility analysis.SETTING: A community hospital general internal medicine clinic, a private internal medicine practice, and a private pulmonary medicine practice. PARTICIPANTS:Sixty-four consecutive patients aged 50 to 75 years awaiting appointments. In order to participate, patients at the pulmonary clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 25 publications
(33 reference statements)
5
24
0
Order By: Relevance
“…27 Whereas the determinants of ethnic differences in ACP and treatment preferences remain unknown, finding differences in relationship quality is itself a compelling reason to focus on improving physicians' relationship with African-American patients. Improving physician training in cultural sensitivity, communication, and relational skills such as building trust and communicating respect for patients will improve perceived health care quality regardless of patient preferences.…”
Section: Discussionmentioning
confidence: 99%
“…27 Whereas the determinants of ethnic differences in ACP and treatment preferences remain unknown, finding differences in relationship quality is itself a compelling reason to focus on improving physicians' relationship with African-American patients. Improving physician training in cultural sensitivity, communication, and relational skills such as building trust and communicating respect for patients will improve perceived health care quality regardless of patient preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Community perspective preferences elicited from a randomly selected sample of the general population of one society or societal subgroup may not be applicable to another, and hence the use of off-theshelf values, even those collected with scientific rigor, must be approached with cautious attention to the underlying samples. Some empirical studies looking specifically at valuation processes have suggested that people think differently about health states depending on their own perspective or outlook on life [1,15,31], which could possibly be influenced by their own health, as well as their age and other demographic characteristics [11,12,14]). Recent work has revealed differences in preferences between the United States and the United Kingdom, possibly attributable to intrinsic ethnic differences in value [32].…”
Section: Discussionmentioning
confidence: 99%
“…These community perspective preferences differ from those that are obtained from a 'patient,' an individual currently experiencing a particular disease or condition, which are termed 'patient' or 'experienced' or 'current health' preferences, and measure the quality of life of the individual providing the score [5]. While it is well-accepted that community perspective preferences differ from patient-perspective scores, research has probed other factors that affect preferences for hypothetical health states including personal experience with the state [1, 7-10] and individuals' age and race (e.g., [11][12][13][14]). An individual's demographic characteristics could affect his or her reference point, which Prospect Theory would suggest affects perspective and hence valuations of hypothetical health states, similar to the effect of health status on preferences [2,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Cykert et al found that African-Americans had a greater preference than Caucasians to remain alive in spite of severe disability. 13 Research comparing African-Americans to Caucasians has found that fewer hospitalized African-Americans have do-not-resuscitate (DNR) directives 14-18 and receive more cardiopulmonary resuscitation (CPR) than do Caucasians. 19 AfricanAmericans have fewer advance directives and living wills [20][21][22] and even believe they may receive less care with a living will.…”
mentioning
confidence: 99%